The concept of critical culture in the book of literature and the discourse of criticism by Abdu al-Salam al-Masada - Maytham Hayawi Abd la Nour Al-Hajji (Zien Journals, 2022)
This study adopts the disclosure of the concept of (critical culture) in the book tagged (Literature and Discourse of Criticism) by the critic Abd al-Salam al-Masadi, whose scientific, intellectual, and critical output has received follow-up, and the attention of critics and researchers at the level of theory and application, especially that the concept of Critical culture has become the focus of attention of critics and writers in light of the cultures of the era that have clearly contributed to building the creative text that reflected the references and mechanisms of human thought amid the influences of science and modern knowledge. According to this vision, critical practice calls for an integrated system of references, mechanisms, and curricula that absorb the creative achievement with its branches. And its extensions and to explore its depths and reveal its fields of knowledge in order to reach the highest levels of creativity. Therefore, it was necessary for the critic to be familiar with the critical and literary cultures of the era in order to keep pace with the intellectual progress in the field of literary criticism with its transformations and changes from one culture to another, and Abd al-Salam al-Masadi has several determinants for this critical culture It will be revealed in this study after we touched on it through careful critical reading of his critical achievement.
Keywords: monetary culture; Russia; book; criticism